Improving Message Embedding by using some Attributes of Color Image - Ahmed Abdullah (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper, we are using enhancing feedback control on a new continuous 4D autonomous hyper chaotic system proposed by Sadiq A. Mehdi and A. Hayder, Qasim [Analysis of a New Hyperchaotic System with six cross-product nonlinearities terms, 2017], this system has three critical points employs ten terms include six quadratic cross-product nonlinearity terms,  We notice that when we apply any linear control method that relies on a single  unit control added to the system, the system behavior in this case cannot control it, so we applied enhancing linear feedback control at origin and we noticed that a necessary condition for suppression is getting positive feedback coefficient. Theoretical analysis and numerical simulation check the validity of the results obtained.